Políticas públicas para el desarrollo rural: un análisis multiescalar - Molina Ibáñez, Mercedes; Farris, Massimiliano (Geographicalia, 2014)
This paper analyses the role of the public policies and of the local society as protagonists of a change necessary for the development of the rural marginal territories at different scales. New economy, rural multifunctionality, territory and public policies constitute the base of this analysis.